IgG subclasses in human immune response to wild and attenuated (vaccine) Junin virus infection - Saavedra, María del Carmen (2003)
Fil: Saavedra, María del Carmen. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Virales Humanas; Argentina.